Effectiveness of a Proposed Strategy Based on Dimensions of Global Mindset in Developing Academic Flow among Students of the Department of Educational and Psychological Sciences - Kareem, Dr. Sarab Mahmood Kareem (Sulaimani Journal for Humanities, 2026)
This study aims to identify the effectiveness of a proposed strategy based on dimensions of the global mindset in developing academic flow among students in the Department of Educational and Psychological Sciences for the academic year 2023/2024 at the College of Education for Humanities, University of Tikrit. To achieve this goal, the researcher formulated three null hypotheses at a significance level of 0.05 and utilized the experimental method with a single experimental group design. The researcher prepared a research instrument, the Academic Flow Scale, consisting of 45 items divided into three dimensions, each with 15 items. The validity of the instrument was confirmed by presenting it to a panel of experts and referees. The research sample was purposively selected and consisted of one group of 90 students from the second year, studying in the morning study system in the Department of Educational and Psychological Sciences at the College of Education for Humanities, University of Tikrit. Appropriate statistical methods were used for data analysis via SPSS software. Based on the results, the researcher reached several conclusions, recommendations, and proposals
Keywords: Proposed strategy; Global mindset; Academic flow